1981
DOI: 10.1177/070674378102600409
|View full text |Cite
|
Sign up to set email alerts
|

Medical and Social Factors Associated with Psychological Distress in a Sample of Community Aged

Abstract: Two hundred persons over 80 in two urban communities were interviewed. Of those interviewed, 21% evidenced psychological impairment as defined by the presence of at least one of the following self-report symptoms: 1) depression; 2) periods of inability to function; 3) suicidal ideation; 4) alcohol problems and 5) use of psychotropic medication. A profile of the psychologically impaired group compared to the psychologically healthy showed that accidents (mostly falls), eye problems and few social contacts were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…A more useful direction for research, which has largely been ignored, is the direct independent effect of social support on health. In fact, some recent studies have found a direct relationship between social support and well-being, irrespective of the presence of stressful life events (Andrews, Tennant, Hewson & Vaillant, 1978;Lin, Ensel, Simeone & Kuo, 1979;Luke, Norton & Denbigh, 1981). Given the present inability of researchers to thoroughly explain the nature of the relationship, a descriptive exploratory design was employed to examine the direct relationship between selected older persons' social support and health in order to identify specific attributes of support which are related to healthy functioning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A more useful direction for research, which has largely been ignored, is the direct independent effect of social support on health. In fact, some recent studies have found a direct relationship between social support and well-being, irrespective of the presence of stressful life events (Andrews, Tennant, Hewson & Vaillant, 1978;Lin, Ensel, Simeone & Kuo, 1979;Luke, Norton & Denbigh, 1981). Given the present inability of researchers to thoroughly explain the nature of the relationship, a descriptive exploratory design was employed to examine the direct relationship between selected older persons' social support and health in order to identify specific attributes of support which are related to healthy functioning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have consistently found that distress or lowered well-being among older people is associated with poor physical status, economic problems and social isolation (Arling 1987;Luke, Norton and Denbigh 1981;Romaniuk, McAuley and Arling 1983). While those with poor health status and impaired functioning on their activities of daily living are the most likely to have lowered mood states, women, whites, the less educated and those living alone are also more often affected (Arling 1987).…”
mentioning
confidence: 99%
“…While those with poor health status and impaired functioning on their activities of daily living are the most likely to have lowered mood states, women, whites, the less educated and those living alone are also more often affected (Arling 1987). A small proportion of older people (2% to 3%) have been diagnosed as having severe depression (Blazer, Hughes and George 1987;Gudand 1976;Luke, Norton and Denbigh 1981), although higher proportions report depressive symptoms (Link and Dohrenwend 1980).…”
mentioning
confidence: 99%
“…31 In Huddersfield, UK, although fewer than 10% of respondents overall avoided activities because of a reluctance to cross the main road, this increased significantly with age, despite almost three fifths of these individuals reporting themselves to be fully mobile. 36 Impact of traffic on social networks Many cross-sectional and longitudinal studies have found evidence of a relationship between social network quality and indicators of poor health, [17][18][19][37][38][39][40][41][42][43][44][45][46] mortality, 14,[20][21][22][23][47][48][49][50][51][52][53] and negative health behaviors more generally. 15,16,[54][55][56] These studies have assessed social network quality in a number of different ways, which would find support in theories of community severance, including the following: numbers of close relationships with friends, acquaintances, relatives, and/or neighbours;…”
Section: Impact On Travelmentioning
confidence: 99%